2019
DOI: 10.25122/jml-2018-0063
|View full text |Cite
|
Sign up to set email alerts
|

Is syncope a predictor of mortality in acute pulmonary embolism?

Abstract: Whether syncope as a presenting symptom independently classifies acute pulmonary embolism (APE) into a high mortality risk group remains a matter of controversy. We retrospectively included all consecutive patients admitted to our clinic with APE from January 2014 to December 2016. Our sample consisted of 76 patients with a mean age of 69 ±13.6 years, 64.5% female. 14.3% presented with syncope at admission. In-hospital mortality was 20.8%. Patients with syncope were more likely to require inotropic support (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[6] A systematic review and meta-analysis based on data from 29 PE studies showed that syncope related to a higher frequency of hemodynamic deterioration and RV dysfunction at presentation, a higher risk of 30-day all-cause cumulative mortality and PE-related adverse outcomes. [8,[13][14][15][16] The absolute risk difference (95% CI) for all-cause death was reported to be 6% (1 to 10%) in studies consisting of unselected population, while it had no impact in PE studies restricted to normotensive patients. [8,[17][18][19][20][21][22] Moreover, the association between syncope and all-cause mortality seems to be stronger than for PE-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[6] A systematic review and meta-analysis based on data from 29 PE studies showed that syncope related to a higher frequency of hemodynamic deterioration and RV dysfunction at presentation, a higher risk of 30-day all-cause cumulative mortality and PE-related adverse outcomes. [8,[13][14][15][16] The absolute risk difference (95% CI) for all-cause death was reported to be 6% (1 to 10%) in studies consisting of unselected population, while it had no impact in PE studies restricted to normotensive patients. [8,[17][18][19][20][21][22] Moreover, the association between syncope and all-cause mortality seems to be stronger than for PE-related mortality.…”
Section: Discussionmentioning
confidence: 99%